SYSTEMATIC REVIEW: CURRENT TRENDS AND RECENT ADVANCEMENTS IN RECONSTRUCTIVE MAXILLOFACIAL SURGERY (CAHIERS MAGELLANES-NS, 2024)
Anomalies in patients with OMF disorders can cause functional and esthetic complications that affect the health of affected individuals by increasing their aspirations, speech and reducing their quality of life. Reconstruction of these defects is one of the most difficult processes, which can be handled in maxillofacial surgery. Historically, the substitute entails of autografts has been considered as the gold standard for regenerative and reconstructive OMF operation. But, with autograft harvesting, the problems like donor-site morbidity, prolongation of the surgery time, and sometimes the non-union of the donor area are faced. This field has benefited from the development of three-dimensional (3D) printing technology, which allows for the possible creation of implants and scaffolds that are molded to the contours of the defect in a particular patient’s body. This review describes the use of 3D printing and VSP for reconstructive maxillofacial surgery operations and their advantages and disadvantages by incorporating 15 studies. It also demonstrates various clinical application cases in which these technologies have been used, showing how they may improve surgical outcomes and patients’ satisfaction.